The Architecture of Persistence: A Defence of Perdurantism against the Problem of Temporary Intrinsics - OGAR, Thomas Eneji; Fidelis, Paalee; George, Aboka (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This paper examines the central metaphysical debate concerning how objects persist through time: endurantism versus perdurantism. Endurantism posits that objects are wholly present at each moment of their existence, enduring through time as three-dimensional entities. In contrast, perdurantism contends that objects are four-dimensional space-time worms, composed of temporal parts, with only a part present at any given time. The core of this inquiry focuses on the “Problem of Temporary Intrinsics”—how a single object can possess contradictory intrinsic properties (e.g., being bent and being straight) at different times without violating the law of non-contradiction. This paper argues that while endurantism aligns with our common-sense intuition of persistence, it fails to provide a satisfactory solution to this problem, resorting to problematic claims about property instantiation being relative to time. Conversely, perdurantism offers a more ontologically parsimonious and logically coherent solution by attributing the different properties to different temporal parts of the same space-time worm. Through a critical analysis of both theories and their responses to this fundamental puzzle, this paper concludes that perdurantism, despite its counter-intuitive nature, presents a superior framework for understanding the metaphysics of persistence and change.